Patients' satisfaction with nursing care quality and associated factors: A cross‐section study - Hanan Fahad Alharbi; Naif S. Alzahrani; Abdulaziz Mofdy Almarwani; Saeed A. Asiri; Fahad M. Alhowaymel (Nursing Open, 2023)
Abstract Aim This research aimed to evaluate patients' satisfaction with the nursing care quality during their hospitalization. Design Quantitative cross‐sectional descriptive design. Methods A convenience sample of 238 patients were recruited from hospitals in two provinces in Saudi Arabia. Patient satisfaction was measured by the Arabic version of the Patients' Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ‐Ar). Results Significant differences were found between Saudi provinces regarding the overall quality of nursing care (M = 4.65, p < 0.001). The study revealed mean significant variations between patient satisfaction with nursing care and sociodemographic factors, including age (p = 0.002), education level (p = 0.047), marital status (p = 0.017), employment status (p = 0.038), urban vs. suburban residence (p = 0.006), length of hospitalization (p = 0.001), and accompaniment by a family member (p = 0.014). Improving patients' experience during their hospitalization requires regular examination of the quality of nursing care services. Patient Contribution This research enhances our understanding of patients satisfaction toward the quality of nursing care received during hospitalization.